2019
DOI: 10.1002/pssa.201800726
|View full text |Cite
|
Sign up to set email alerts
|

Rare Earth Doping of Topological Insulators: A Brief Review of Thin Film and Heterostructure Systems

Abstract: Magnetic topological insulators (MTIs) are a novel materials class in which a topologically nontrivial electronic band structure coexists with long-range ferromagnetic order. The ferromagnetic ground state can break time-reversal symmetry, opening a gap in the topological surface states whose size is dependent on the magnitude of the magnetic moment. Doping with rare earth ions is one way to introduce higher magnetic moments into a material, however, in Bi 2 Te 3 bulk crystals, the solubility limit is only a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 96 publications
1
15
1
Order By: Relevance
“…Previous XAS and XMCD studies of Bi 2 Te 3 thin films doped with RE ions other than Eu revealed a 3+ valence of the dopants 13,15,17,[20][21][22]55 , in strong contrast with the 2+ valence of the Eu ions found here. This is likely due to the half-filled 4f shell of Eu 2+ , [Xe] 4f 7 , having a very stable Hund's rule ground state ( 8 S 7/2 ) with no spin-orbit splitting and a large spin magnetic moment arising from 7 unpaired electrons.…”
Section: Resultscontrasting
confidence: 90%
See 2 more Smart Citations
“…Previous XAS and XMCD studies of Bi 2 Te 3 thin films doped with RE ions other than Eu revealed a 3+ valence of the dopants 13,15,17,[20][21][22]55 , in strong contrast with the 2+ valence of the Eu ions found here. This is likely due to the half-filled 4f shell of Eu 2+ , [Xe] 4f 7 , having a very stable Hund's rule ground state ( 8 S 7/2 ) with no spin-orbit splitting and a large spin magnetic moment arising from 7 unpaired electrons.…”
Section: Resultscontrasting
confidence: 90%
“…The highest effective magnetic moment of 12.6µ B was observed at 2 K for (Dy x Bi 1−x ) 2 Te 3 with x = 0.023 20 . However, the magnetic moment of the Dy ions was found to be strongly concentration dependent, in contrast to Gd and Ho dopants in Bi 2 Te 3 thin films, possessing an effective magnetic moment of ∼ 7µ B (close to the maximum free ion value) and of ∼ 5.15µ B (half of the theoretical maximum moment), respectively 13 . Despite these large magnetic moments, most investigations found no long-range FM order down to 2 K and thus no gap opening in the TSS 16,21,22 .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Further, with the formation of ferromagnetic state only at the surface, a state which leads to opening the gap, has been confirmed for the Mn doped Bi 2 (Te,Se) 3 as well as for the Cr-doped (Bi,Sb) 2 Te 3 thin films [ 26 ]. Bi 2 Te 3 doped with rare earth is discussed mostly from the point of view of modifying the thermoelectric properties [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Controlling the distribution of magnetic dopants within the TI’s matrix resulting from sample preparation procedures and chemical potentials of the constituent atoms is still challenging and requires in-depth and careful characterizations at the atomic level.…”
Section: Introductionmentioning
confidence: 99%
“…Since the size of the band gap is directly proportional to the magnetic moment in TRS-broken TI materials, doping with rare earth (RE) elements such as Dy, which has a large atomic moment of up to 10.5 μ B , has been considered an alternative approach to raise the QAHE temperature. 7 Contrary to most other RE dopants such as Gd and Ho, which show a constant atomic moment independent of doping concentration, 8 , 9 a large atomic moment is found in Dy:Bi 2 Te 3 (DBT) films for low doping concentrations, thereby having the potential to be less detrimental to the electrical transport properties. 10 This can be explained by possible antiferromagnetic (AFM) coupling between Dy atoms for higher concentrations, reminiscent of the behavior of elemental Dy.…”
mentioning
confidence: 99%